An Overview of Gender Equality in Egypt - Hend HASSAN (European Journal of Interdisciplinary Studies, 2019)
Unlike the majority of ancient societies, Egypt held women at a very high eminence rendering them equitable status with men. Ancient Egyptian women possessed equal legal as well as political rights as men, the matter that has been expressed through a lot of Egyptian art and manuscripts. At a certain point in history Egyptian women ruled the country as queens and pharaohs. Unfortunately, moving into the present time the status of women in Egypt shows a profound retreat. Empowering women and incorporating them as vital members and partakers in all realms of life is not a luxury anymore but rather a necessity. Regrettably, gender inequality in Egypt remains to be a fundamental barrier hindering the accomplishment of this goal. It is the aim of this paper to shed light on the current situation of women in Egypt through comparisons with other neighbouring countries as well as with global indices at present. Conclusions show that despite some improvements, a lot remains to be done in order to ensure gender equality that is required to endorse sustainable development goals in Egypt.